(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This academic paper explores the fundamental principles and critical importance of suturing techniques in the context of facial and jaw surgeries. The face and jaw area present unique challenges due to their aesthetic significance and functional complexities. The paper delves into the various suturing methods employed in these delicate regions, emphasizing the significance of precise and meticulous techniques to achieve optimal wound closure and minimize complications